Novel heterozygous mutation in COL4A4 responsible for Alport syndrome in a Chinese family - Du, Ran; Liu, Jishi; Hu, Yiqiao; Peng, Song; Fan, Liangliang; Xiang, Rong; Huang, Hao (Frontiers in Genetics, 2022)
Background: Chronic kidney disease, a global public health problem, results in kidney damage or a gradual decline in the glomerular filtration rate. Alport syndrome is commonly characterized by chronic glomerulonephritis caused by a structural disorder in the glomerular basement membrane. Currently, three disease-causing genes, namely collagen type IV alpha 3–5 (COL4A3, COL4A4, and COL4A5), have been associated with the occurrence of Alport syndrome. Methods: We enrolled a Chinese family where the affected individuals suffered from recurrent hematuria and proteinuria. The proband was selected for whole-exome sequencing to identify the pathogenic mutations in this family. Results: After data filtering, a novel heterozygous COL4A4 variant (NM_000092: c.853G>A/p. G285A) was identified as the putative genetic lesion in the affected individuals. Further co-segregation analysis using Sanger sequencing confirmed that this novel COL4A4 mutation (c.853G>A/p. G285A) exists only in the affected individuals and is absent in other healthy family members as well as in the control cohort of 200 individuals from the same locality. According to American College of Medical Genetics and Genomics guidelines, the mutation was classified as ‘potentially pathogenic’. A bioinformatics-based prediction analysis revealed that this mutation is pathogenic and may disrupt the structure and function of type IV collagen. This variant is located at an evolutionarily conserved site of COL4A4. Conclusions: In this study, we identified a novel heterozygous COL4A4 variant (c.853G>A) in a Chinese AS family and assisted to diagnose this AS proband as autosomal-dominant Alport syndrome (ADAS). Our study expands the spectrum of Alport syndrome mutations and contributes to the genetic counseling and diagnosis of patients with Alport syndrome.